Comparison of dexmedetomidine and remifentanil on reducing coughing during emergence from anesthesia with tracheal intubation: A meta-analysis - Fan, Xing; Cai, Hai; Pan, Bingbing; Xie, Yubo (Frontiers in Pharmacology, 2022)
Background: Dexmedetomidine and remifentanil are well known to suppress airway reflex during emergence from anesthesia, but which one is more effective is unclear. We conducted a meta-analysis to compare the effect of dexmedetomidine and remifentanil on reducing the occurrence of coughing. Design: meta-analysis. Methods: We systematically searched PubMed, Embase, and Cochrane Library for randomized controlled trials (published between January 1, 1950, and December 30, 2021; no language restrictions) comparing dexmedetomidine infusion with remifentanil infusion. The primary endpoint was the incidence of moderate to severe coughing during the recovery period. The secondary endpoints were the time of recovery and extubation, and residual sedation. We assessed pooled data by using a random-effects model. Results: Eight studies with 502 participants were included. The meta-analysis showed no statistically difference between dexmedetomidine and remifentanil in the occurrence of moderate to severe coughing during emergence from anesthesia (OR 1.45 ,95%CI 0.62 to 3.38), the extubation time (MD 0.93 minutes, 95%CI -0.28 to 2.14), and the residual sedation (OR 2.52, 95%CI 0.92 to 6.91). Compared with dexmedetomidine, the average recovery time of remifentanil was shorter (MD 3.88 minutes, 95%CI 1.01 to 6.75). Conclusion: Dexmedetomidine and remifentanil infusion had no difference in the occurrence of moderate to severe coughing during emergence from anesthesia.